Different Methods for Long-term Systematic Assessment of Challenging Behaviors in People with Severe Intellectual Disability - Delgado, Candida; Gonzalez-Gordon, Rodrigo G.; Aragón, Estívaliz; Navarro, Jose I. (Frontiers in Psychology, 2017)
The aim of this study was to compare the advantages and disadvantages of different behavioral assessment procedures with the purpose of design a long-term assessment procedure that brings together the benefits observed. The study involved four adults with severe and profound intellectual disabilities and severe behavioral problems. A behavioral assessment has been carried out with Scatter Plot, Antecedent-Behavior-Consequence record sheets and, finally, The Observer XT. We conducted a comprehensive assessment of challenging behavior of each participant, by reviewing bio-psychosocial records, interviewing family and direct caregiver staff, as well as direct observation. A large inter-subject behavior variability and instability of intra-subject behavior were found, raising questions about the election of the period to evaluate. The first evaluation level highlighted information about stability of behavior, the second level stand out the context in which it occurs and the third level detailed the different topographies of each behavioral category. The results suggest the desirability of a continuous assessment by combining these three levels for adjusting to the specific characteristics of behavior. We suggest the need of designing a single behavioral assessment procedure that includes the benefits observed in each of the instruments used.